Breast cancer-related lymphedema: A literature review for clinical practice - Ausanee Wanchai; Jane M. Armer; Bob R. Stewart; Bonnie B. Lasinski (Elsevier, 2016)
Lymphedema is the swelling of soft tissues as a result of the accumulation of protein-rich fluid in extracellular spaces. Secondary lymphedema is precipitated by an event causing blockage or interruption of the lymphatic vessels. Secondary lymphedema is a potential complication that may affect the quality of life of patients treated for breast cancer. Life-long risk factors of post-breast cancer lymphedema are related to the extent of axillary node involvement, type of breast surgery, and radiation therapy. These factors decrease lymphatic drainage and increase stasis of fluids in the areas of skin and subcutaneous tissues that drain to regional lymph nodes. Breast cancer-related lymphedema can involve the arm and hand, as well as the breast and trunk on the operative side. Clinical symptom assessment and circumferential measures are widely used to evaluate lymphedema. Treatment of lymphedema associated with breast cancer can include combined modality approaches, compression therapy, therapeutic exercises, and pharmacotherapy.